Molecular genetic methods for identifying raw materials in meat products: Diversity, opportunities and prospects - I. V. Safenkova; N. L. Vostrikova; N. A. Taranova; E. A. Zvereva; B. B. Dzantiev; A. V. Zherdev (Теория и практика переработки мяса)
In the current economic situation, after easing the Covid pandemic restrictions, almost all laboratories, which are focused on evaluation of the conformity of food products, have faced issues in supplying for their laboratories. In this regard, in the last years many laboratories have been forced to validate new approaches and introduce new methods for assessing conformity of the food products. Very often it is not possible to use only one method to resolve the issue of the food product ingredients, especially for the purpose of traceability of their names and the used raw materials, listed on the label. Survey of the raw food materials to determine whether they correspond to the type name is a simpler task, in contrast to survey of the multicomponent food product. Many researchers have to estimate the opportunities and feasibility of application of various methodologies in their workplaces. Therefore, this review is relevant for the researchers in this field, as it focuses on aspects and special features of similar methodologies. The prospect of molecular genetic methods for identification of the raw materials used for manufacturing of meat products is presented below. This review also represents characteristics of methods for identification of the sources of raw materials used for the manufacturing of the meat products, based on the recognition of species-specific sections within the nucleic acids structures. The variety of methods (hybridization methods, polymerase chain reaction, different types of isothermal amplifications, methods using CRISPR/Cas systems), the principles of their implementation, and achieved analytical characteristics are considered. The capacities and competitive potential of various methods are discussed, as well as approaches being developed to overcome the existing limitations.